Pediatric brain abscess with fatal outcome caused by hypervirulent Klebsiella pneumoniae, serotype K2-ST65 - Emily Tan Sheau En; Nabilah Ismail; Nur Syafiqah Mohamad Nasir; Yasmin Khairani Muhammad Ismadi; Nik Mohd Noor Nik Zuraina; Siti Asma' Hassan (Elsevier, 2023)
Hypervirulent Klebsiella pneumoniae (hvKp) is an emerging pathotype in addition to classical Klebsiella pneumoniae, with its ability to cause life-threatening, community-acquired metastatic infections even in healthy individuals. We presented a case of cerebral abscess preceded by otitis media in a 10-year-old child caused by hvKp. The isolates from blood pus aspirate were later identified as K. pneumoniae capsular serotype K2 and closely related to sequence type (ST65), with multiple hypervirulent genes detected (rmpA, rmpA2, iucA and peg344). She succumbed to death despite surgical drainage and susceptible antibiotic therapy. Clinicians should be cognizant of the rising incidence of hvKp infections in pediatric populations.